Associations among meniscal damage, meniscal symptoms and knee pain severity. Issue 6 (June 2017) - MacFarlane, L.A.; Yang, H.; Collins, J.E.; Guermazi, A.; Jones, M.H.; Teeple, E.; Xu, L.; Losina, E.; Katz, J.N.
Summary: Objective: Meniscal tears occur frequently in patients with knee osteoarthritis (OA). The aim of our study was to determine whether meniscal damage identified on magnetic resonance imaging (MRI) is associated with the severity of knee pain or the frequency of meniscal symptoms in patients with knee OA. Methods: We performed a cross-sectional study using data from the Meniscal Tear in Osteoarthritis Research (MeTeOR) trial. We characterized meniscal damage hierarchically as: root tear; maceration; long and short complex or horizontal tears; and simple tears. Subjects completed the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) Pain Scale and a survey of frequency of meniscal symptoms. We used multivariable general linear models to assess the relationships between meniscal damage and 1) pain severity; and 2) meniscal symptoms, after adjusting for demographic and radiographic features. In further analysis root tear was considered as a binary variable. Results: Analysis included 227 knees. Root tears were present in 19%, maceration in 14%, long complex or horizontal tears in 22%, short complex or horizontal tears in 30%, and simple tears in 14%. Root tears were associated with higher WOMAC pain scores. The adjusted mean WOMAC pain score was 45.2 (standard error (SE) 2.7) for those with root tear and 38.7 (SE 1.2) for subjects without root tear ( P  = 0.03). We did not find statistically significant associations between meniscal morphology and frequency of meniscal symptoms. Conclusion: Root tears were associated with greater pain than meniscal tears or maceration. We did not find a relationship between meniscal damage and meniscal symptoms.